Escherichia coli acyl-CoA dehydrogenase inhibitors and genetic engineering for short chain alkane production - Bajko, Paulina (2019)
The depletion of fossil fuels is an increasing problem, which drives the search for an alternative, sustainable and cost-effective methods. Due to advancements in genetic engineering, genetically modified microbes (e.g. Escherichia coli) receive more attention as potential “fuel factories”. The "hot topic", in the field, is an alteration of the fatty acid metabolism. In 2013 the production of short-chain alkanes (in other words petrol) by genetically modified E. coli was reported. Up to date, the only genetic modification was utilized as a tool for microbial metabolism manipulation. This project aims to build a library of potential chemical acyl-CoA dehydrogenase inhibitors and establish their potency. Pantothenic acid was used as a scaffold for total synthesis of inhibitors such as 2-pentynoyl-S-pantetheine. Unlike previous studies where protection group chemistry and hydroxybenzotriazole, N,N'-dicyclohexylcarbodiimide mediated amide coupling. A simple four-step synthesis was achieved with 1`,1`-carbonyldiimidazole as a coupling agent. The utilisation of this approach decreased the number of steps which resulted in higher yields, as well as reduced overall cost and toxicity of by-products. These factors are important if the proposed technique was to be used for industrial applications. During this study synthesis and purification of 28 S-acyl pantetheines was achieved. The potency of the inhibitors was tested on overexpressed and purified FadE. E. coli protein was overexpressed in E. coli BL21 strain and purified by Styrene Maleic Acid-Lipid Particles technique and affinity chromatography. Protein activity was assessed with ferrocenium hexafluorophosphate assay. Synthesised pantetheines exhibit different levels of activity. 2-Pentynoyl-S-pantetheine proved to be the most potent compound with the half maximal inhibitory concentration of 0.04 mM. The fatty acid metabolism regulator protein (FadR) is responsible for the regulation of fatty acid metabolism, to lift this regulation knockout with the λ-red technique was achieved. Two plasmids carrying genes for fatty acyl-ACP thioesterase, fatty acyl-CoA synthetase, fatty acyl-CoA reductase and fatty aldehyde decarbonylase were also developed.